(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: In Pakistan general practitioners (GPs) are self-employed medical doctors, who work independently and establish their own clinics usually in their hometowns. Compared to other clinical disciplines, however, general practice has produced significantly less published research in terms of both researchers and subjects. Our objective was to assess the attitude of self-employed GPs towards medical research. Materials and methods: Cross-sectional survey was conducted in the districts of Lodhran and Bahawalpur in Punjab from May to Oct, 2012. Convenience sampling technique was used to select these GPs. Data was recorded on the questionnaires, collected through personal interviews with every GP. Results: The mean age among the doctors was 43.44+8.63 years. All doctors were males. 87% of the rural and 59% of the urban doctors had no postgraduate medical qualification. Mean duration of general practice was 10.05+6.96 years. Only 30.2% (n=19) read any medical journal regularly whereas 49.2 % (n=31) read occasionally, 14.2% (n=9) have no interest in reading of the medical journals. 31.7% (n=20) of the respondents mentioned overwork in clinical practice as the main reason for non-participation in research activities. Whereas 12.7 % (n=8) mentioned financial constraints while 19.1(n=12) of the respondents find no personal benefits in medical research. Lack of infrastructure was mentioned by only 9.5% of the respondents. Conclusion: Overall this study identified that many of the GPs had a poor attitude for medical research in particular; rather than just lack of the facilities. Overwork in clinical practice, financial constraints and lack of personal benefits were the main reason for non-participation in research activities.